Embodied shame : uncovering female shame in contemporary women's writings - Bouson, J. Brooks (State University of New York Press, 2009)
"How does physical, emotional, and sexual abuse shape women's perceptions of their bodies and identities? How are women's psyches affected by the sexual, racial, and cultural denigration that occurs when women's bodies are represented as defective, spoiled, damaged, or dirtied? Embodied Shame skillfully explores these questions in the context of recent writings by North American women, contributing to work in shame theory and to feminist analyses of the intersections of theories of the body, affect, emotions, narrative, and trauma. By examining popular contemporary fictional - and nonfictional - texts, including Alice Munro's Lives of Girls and Women, Dorothy Allison's Bastard Out of Carolina, Toni Morrison's The Bluest Eye, Edwidge Danticat's Breath, Eyes, Memory, and Lucy Grealy's Autobiography of a Face, J. Brooks Bouson illuminates how deeply entrenched bodily shame continues to operate in contemporary culture, even as we celebrate the supposed freeing of the female body from the social and cultural constraints that have long bound it."--Jacket